Acute decompensation (AD) of advanced chronic liver disease (ACLD) and hepatitis E virus (HEV) infection as the trigger - Skladaný, Ľubomár; Adamcová Selčanová, Svetlana; Janičko, Martin; Bečková, Zuzana; Helmová, Lenka; Vnenčáková, Jana (Klinicka mikrobiologie a infekcni lekarstvi, 2018)
INTRODUCTION: HEV infection is perceived as the cause of acute hepatitis in endemic areas. In addition, it may also manifest as a possible trigger of AD or acute-on-chronic liver failure (ACLF). OBJECTIVES: To determine the prevalence of HEV infection as a trigger of AD/ACLF in patients admitted for decompensated ACLD (dACLD). METHODS: A retrospective study; data analysis of consecutive patients with dACLD admitted to a liver unit. Study interval: August 2016 - October 2017. INCLUSION CRITERIA: AD, defined as the interval between the first manifestations of decompensation and admission ≤ 4 weeks; an anti-HEV ELISA antibody assay in the IgG and IgM classes (HEV Ab ELISA, DRG Instruments GmbH, Germany). EXCLUSION CRITERIA: chronic decompensation of liver cirrhosis, insufficient data. Recorded variables: gender, age, etiology of ACLD, Model for End-Stage Liver Disease (MELD) score, Child-Turcotte-Pugh score (CTPS), anti-HEV IgG and IgM, ACLF 0-3, length of stay (LOS) in the hospital, mortality: in-hospital mortality (IHM), 30-day, 6-month, 1-year and overall mortality. RESULTS: Over the 15-month study interval, a total of 212 patients (pts) were admitted for dACLD, including 115 with AD (54 %). The final analysis comprised 91 pts with a mean age of 53.3 years (y); 56 % were men. ETIOLOGY: ALD 81 %, autoimmune diseases 7 %, HCV 5 %, non-alcoholic steatohepatitis 3 %, HBV 2 %, others 2 %. The mean MELD score and CTPS were 22.5 and 10.5 points (p), respectively. HEV infection as a possible trigger of AD was found in 9 % of pts (AD 75 %, ACLF 1-12.5 %, ACLF 3-12.5 %). Between HEV-positive and HEV-negative patients, there were no significant differences in age (p = 0.11), gender (p = 0.13), median MELD score (p = 0.42), median CTPS (p = 0.57), LOS (p = 0.56), overall survival (p = NS), IHM (p = NS), 30-day (p = NS), 6-month (p = NS), 1-year (p = NS) and overall mortality (p = NS). CONCLUSION: The prevalence of HEV infection as a trigger of AD was 9 %. There were no significant differences in recorded variables, including mortality, between HEV-negative and HEV-positive patients.
Keywords: jaterní cirhóza; Humans; Middle Aged; lidé středního věku; lidé; retrospektivní studie; akutní zhoršení chronického selhání jater; mužské pohlaví; virus hepatitidy E; Female; Hepatitis E; Male; Liver Cirrhosis; Retrospective Studies; Hepatitis E virus; hepatitida E; ženské pohlaví; Acute-On-Chronic Liver Failure